Price dispersion, chain heterogeneity, and search in online grocery markets - Xulia González; Daniel Miles-Touya (SERIEs - Journal of the Spanish Economic Association, 2018)
This paper identifies patterns of cross-sectional and temporal price dispersion-in the Spanish online grocery retail market-and evaluates the extent to which search costs and chain heterogeneity explain such dispersion. We build a data set comprising 836,074 prices for the most popular grocery products sold online by Spanish national chains at different locations. Our results show that price dispersion is still present (albeit to a lesser extent) even after controlling for chain heterogeneity and that it persists over time. We structurally estimate search costs distributions for two different baskets of goods using price data while accounting for vertical product differentiation. The analysis suggests that the extent of search is low. According to our estimates more than two thirds of consumers do not compare prices among supermarkets. We also find that more frequently purchased products have lower search cost and also lower price-cost margins.
Keywords: D4; D83; L11; 330; Price dispersion; Retail food market; Pricing strategies; Search costs